Kesedaran membayar zakat pendapatan di Malaysia - Hairunnizam Wahid,; Sanep Ahmad,; Mohd Ali Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2007)
In Malaysia, the National Fatwa Council has decreed that it is compulsory upon the Muslims in Malaysia to pay the Islamic alms tax from their incomes. This study attempts to evaluate the awareness of paying the Islamic alms tax on income among Muslims in Malaysia, and it further identifies the factors influencing their awareness. The premier data are gathered and utilized for this study. The data are analyzed using logistic regression technique. The result shows that the awareness of paying the Islamic alms tax among the Muslims on their incomes is still low, and the demographic factors such as age, sexes, marital status, education level and income level as well as the mechanism employed to collect the Islamic alms tax significantly influence the payment of the Islamic alms tax on income. This study proposes some policy implications for improving the collection of the Islamic alms tax on income in Malaysia such as increasing awareness program and employer's cooperation